"Omelora": Orthodox and Disciplinary Masculinities in Chimamanda Ngozi Adichie's Purple Hibiscus. (October 2022) - Umezurike, Uchechukwu P.
This paper examines the connections between masculinity and orthodoxy in Chimamanda Ngozi Adichie's Purple Hibiscus to underscore the intersections of gender, class, religion, and ethnicity. Adichie depicts two contradictory figures of Catholic orthodoxy, namely, Eugene and Father Amadi and the consequences of their performances of masculinity. Where Eugene enacts violence on his family in the name of piety, Father Amadi demonstrates receptivity to human suffering as crucial to piety. I draw on the ideas of Michel Foucault and Raewyn Connell to demonstrate how discipline, control, and male power operate in the domestic sphere and their effects on subjectivities and bodies. Adichie's portrayal of Eugene articulates a model of disciplinary power undergirded by orthodoxy. Eugene, therefore, dramatizes orthodox masculinity. I argue that Adichie envisions a redefinition of masculinity by presenting Father Amadi as an alternative to Eugene's enactments of orthodoxy. I conclude that Adichie provides us with an understanding of how people can deploy violence in the name of piety and religion. Indeed, Adichie emphasizes the need to redefine masculinity cognizant of the dignity of all humanity.